THE OF LEARNING ABILITY IN THE GAME SEPAKTAKRAW - Ruslan, R (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
This experimental research aims to determine the effect of teaching methods and learning motivation against the precepts football ability in the game sepaktakraw. Motivation to learn is divided into two parts, high and low. This research was conducted in the Prodi Health Physical Education and Recreation, FKIP Mulawarman University, the academic year 2015/2016. Experimental method using a 2x3 factorial design. The sample consisted of 60 students were divided into six groups, each consisting of 10 mahsiswa. The data analysis technique is a two-way analysis of variance (ANOVA) followed by Tukeys test at a significance level Î± = 0:05. The results of this study indicate that (1). Teaching methods massed practice the higher the effect of learning methods distributed practice against football ability precepts in the game sepaktakraw, (2) learning methods massed practice lower influence of learning methods combined (mixed) against football ability precepts in the game sepaktakraw, (3) Methods of learning distributed practice lower influence of learning methods combined (mixed) against football ability precepts in the game sepaktakraw, (4) There is interaction between the learning methods massed practice, learning methods distributed practice, learning methods combined (mixed) and the motivation to learn the football ability precepts in game sepaktakraw, (5) teaching methods massed practice higher learning methods distributed practice against football ability precepts in the game sepaktakraw on group learning motivation high, (6) Methods of learning massed practice lower than learning methods distributed practice against football ability sila in the game sepaktakraw on group learning motivation high, (7) learning methods of distributed practice is lower than learning methods combined (mixed) against football ability precepts in the game sepaktakraw on group learning motivation high, (8) teaching methods massed practice higher learning methods distributed practice the football ability precepts in the game sepaktakraw in the group of low learning motivation, (9) teaching methods massed practice lower than learning methods distributed practice against football ability precepts in the game sepaktakraw in the group of low learning motivation, and (10) learning methods of distributed practice lower of learning methods combined (mixed) against the precepts football ability in the game sepaktakraw group low learning motivation.